The C2 domains of granuphilin are high-affinity sensors for plasma membrane lipids - Lyakhova, Tatyana A. (2013)
Membrane-targeting proteins are crucial components of many cell signaling pathways, including the secretion of insulin. Granuphilin, also known as synaptotagmin-like protein 4, functions in tethering secretory vesicles to the plasma membrane prior to exocytosis. Granuphilin docks to insulin secretory vesicles through interaction of its N-terminal domain with vesicular Rab proteins; however, the mechanisms of granuphilin plasma membrane targeting and release are less clear. Granuphilin contains two C2 domains, C2A and C2B, that interact with the plasma membrane lipid phosphatidylinositol-(4,5)-bisphosphate [PI(4,5)P(2)]. The goal of this study was to determine membrane-binding mechanisms, affinities, and kinetics of both granuphilin C2 domains using fluorescence spectroscopic techniques. Results indicate that both C2A and C2B bind anionic lipids in a Ca(2+)-independent manner. The C2A domain binds liposomes containing a physiological mixture of lipids including 2% PI(4,5)P(2) or PI(3,4,5)P(3) with high affinity (apparent K(d,PIPx) of 2-5 nM), and binds nonspecifically with moderate affinity to anionic liposomes lacking phosphatidylinositol phosphate (PIP(x)) lipids. The C2B domain binds with sub-micromolar affinity to liposomes containing PI(4,5)P(2) but does not have a measurable affinity for background anionic lipids. Both domains can be competed away from their target lipids by the soluble PIP(x) analogue inositol-(1,2,3,4,5,6)-hexakisphosphate (IP(6)), which is a positive regulator of insulin secretion. Potential roles of these interactions in the docking and release of granuphilin from the plasma membrane are discussed.